Localisation of Manganese Accumulated by Microalgal Cells Using Energy-Dispersive X-ray Microanalysis in the Electron Microscope - Abu-Shammala, Farida (Asian Journal of Chemistry, 2012)
The sites of accumulation of manganese in cells of the unicellular chlorophyte algae Chlamydomonas and Chlorella, and the blue-green alga Anabaena, have been determined by energy-dispersive X-ray microanalysis of freeze-dried cryosection in a scanning transmission electron microscope. Following exposure of that cells to a solution containing 200 ppm manganese for 24 h, static analyses of cellular compartments and digital X-ray mapping of element distributions in the cryosections showed that the manganese was nearly all concentrated in electron-dense granules within the cells. In Anabaena, however, large amounts of Mn were also found in the gelatinous sheath in which many of the blue-green cells were enveloped. Binding of manganese in the cell wall, except in the external mucilaginous layer in Anabaena, could not be demoustrated. The manganese concentration in the granules was highest in Chlamydomonas cells, averaging about 10% by weight. The intercellular bodies, presumed to be polyphosphate inclusions because of the presence of high concentrations of p and O, also contained mg and some C. In Chlorella cells, these elements were accompanied by Na, S, Cl and K and in Anabaena by Ca. The mean calculated O : P stoichiometry from analyses of individual granules was about 1 : 9 : 1 for Chlorella, and > 3 : 1 for Chlamydomonas and Anabaena. Measurements of the O : P ratio with time, and analyses of some cells ai low temperature, suggested that observed O : P stoichiometries below 4 : 1 could not be explained simply by beam-induced loss of oxygen during analysis. Thus P in the granules must be present in forms other than simple phosphate. The deposition of manganese in interacellular granules, and the trapping of mn in the external mucilage in the blue-green alga, appear to be mechanisms by which the alga cells can reduce toxic physiological effects of the element.